Lower extremity movement patterns and variability in adolescent athletes with lateral ankle sprain history during drop vertical jump - Ha, S.; Lee, I.; Kim, J.-N. (Korean Journal of Sport Biomechanics, 2023)
Objective: This study examined differences in joint kinematics and movement variability of lower extremity between adolescent athletes with and without lateral ankle sprain (LAS) history during drop vertical jump. Method: Fourteen adolescent athletes with LAS history and 14 controls participated in this study. The independent variable was group while dependent variables were 3D joint kinematics and movement variability of hip, knee, and ankle joint. Ensemble curve analyses were conducted to identify differences in movement strategies between two groups. Results: The LAS group showed that greater eversion during jump phase compared with the control group. Additionally, less movement variability was found in the LAS group during the pre-landing and jump phases in ankle and hip joints compared with the control group. Conclusion: The LAS group may adapt the environmental constraints by reducing the movement variability in ankle and hip joints. However, training programs focusing on recovery of ankle function should be emphasized after LAS because excessive pronation for prevention of LAS during the jump phase may result in reduced performance.